2013
DOI: 10.1080/13683500.2012.665045
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of past experience in the formation of a tourist destination's image and in tourists’ behavioural intentions

Abstract: The aim of this work is to understand the moderating effects of tourists' prior experiences of a given destination on the process of image formation (in both its cognitive and affective dimensions) for that destination and on the influence that the imagetogether with the tourist's satisfaction -has on their loyalty-driven behaviours as expressed in the intention to recommend. To achieve this aim, a sample of 512 tourists was used and a multi-group analysis performed, distinguishing between first-time and repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 72 publications
3
28
1
Order By: Relevance
“…The results show that the influence of self‐congruity on perceived value is greater among tourists with previous destination experience than among first‐time visitors. This outcome reflects the findings of earlier studies reporting that increased familiarity is associated with a more positive destination image (Baloglu, ; Fridgen, ; Ahmed, ; Rodríguez‐Molina et al, ). The better the match between the destination image and self‐image among repeat visitors, the greater the influence on the perceived value of the destination they have visited.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results show that the influence of self‐congruity on perceived value is greater among tourists with previous destination experience than among first‐time visitors. This outcome reflects the findings of earlier studies reporting that increased familiarity is associated with a more positive destination image (Baloglu, ; Fridgen, ; Ahmed, ; Rodríguez‐Molina et al, ). The better the match between the destination image and self‐image among repeat visitors, the greater the influence on the perceived value of the destination they have visited.…”
Section: Discussionsupporting
confidence: 88%
“…The proposed model (see Figure ) was estimated using SmartPLS 3 statistical software, developed by Ringle, Wende, and Becker (). Table shows the adequate psychometric properties of the scales used to measure the 12 first‐order constructs in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the findings suggest that personal experience with the destination resulted in greater overall attractiveness and higher visit intentions. These results confirm previous studies (Kim et al, ; Rodríguez Molina et al, ). In addition, in line with Lepp and Gibson (), the findings show that previous experience with other long‐haul destinations may engender confidence for future travel, thus influencing loyalty (Sönmez & Graefe, ; Lepp & Gibson, ).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies also demonstrated a positive relationship between previous travel experience and loyalty (Sönmez & Graefe, ; Oppermann, ; Pearce & Kang, ). Specifically, as experience with a destination increases, tourists' intentions to revisit the destination in the future also increase (Chen & Lin, ; Rodríguez Molina, Frías‐Jamilena, & Castañeda‐García, ). In addition, individuals with travel experiences in various destinations may become more confident and be more likely to revisit those places (Chi, ).…”
Section: Literature Reviewmentioning
confidence: 99%